1999
DOI: 10.1093/ajcn/69.2.231
|View full text |Cite|
|
Sign up to set email alerts
|

Cholesterol-lowering effects of a proprietary Chinese red-yeast-rice dietary supplement

Abstract: Red yeast rice significantly reduces total cholesterol, LDL cholesterol, and total triacylglycerol concentrations compared with placebo and provides a new, novel, food-based approach to lowering cholesterol in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
335
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(359 citation statements)
references
References 13 publications
8
335
0
8
Order By: Relevance
“…The statins have repeatedly been shown to reduce mean serum LDL-C concentrations by 28 -35% in long-term trials (10)(11)(12), with corresponding reductions in cardiovascular death of 23 -32% in both primary and secondary prevention trials (11,12). A previous study showed that red yeast rice resulted in significant reductions in LDL-C (1.00 mmol/l), total cholesterol (1.09 mmol/l) and triglycerides (0.17 mmol/l) levels (2). In this study, Monascus purpureus Went rice resulted in significant reductions in LDL-C (1.59 mmol/l (30.6%)), total cholesterol (1.73 mmol/l (23.7%)) and triglycerides (0.21 mmol/l (13.4%)) levels from baseline to week 4.…”
Section: Discussionmentioning
confidence: 97%
“…The statins have repeatedly been shown to reduce mean serum LDL-C concentrations by 28 -35% in long-term trials (10)(11)(12), with corresponding reductions in cardiovascular death of 23 -32% in both primary and secondary prevention trials (11,12). A previous study showed that red yeast rice resulted in significant reductions in LDL-C (1.00 mmol/l), total cholesterol (1.09 mmol/l) and triglycerides (0.17 mmol/l) levels (2). In this study, Monascus purpureus Went rice resulted in significant reductions in LDL-C (1.59 mmol/l (30.6%)), total cholesterol (1.73 mmol/l (23.7%)) and triglycerides (0.21 mmol/l (13.4%)) levels from baseline to week 4.…”
Section: Discussionmentioning
confidence: 97%
“…Red yeast rice, prepared by adding purple-colored yeast (Monascus purpureus) to steamed rice, has been consumed in China for thousands of years to improve digestion and blood circulation. Among its many constituents, this fermented mix contains molecules called statins, which have a high affinity for 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) 3 reductase, a rate-limiting enzyme in cholesterol biosynthesis pathway (1)(2)(3)(4). The statins derived from red yeast rice fermentation include lovastatin, mevastatin, simvastatin (a methyl derivative of lovastatin), and pravastatin; whereas fluvastatin, atorvastatin, cerivastatin, rosuvastatin, and pitavastatin are synthetic compounds.…”
mentioning
confidence: 99%
“…Heber i wsp. przeprowadzili prospektywne, kontrolowane placebo badanie obejmujące 83 nieleczonych pacjentów z hipercholesterolemią [21]. U chorych stosowano preparat RYR w dawce 2,4 g przez 12 tygodni.…”
Section: Monakolina -Od Starożytności Do Współczesnościunclassified